Fendas orofaciais no recém-nascido e o uso de medicamentos e condições de saúde materna: estudo caso-controle na cidade do Rio de Janeiro, Brasil Oral clefts in the newborn and medical intakes and maternal health conditions: a case-control study in the city of Rio de Janeiro, Brazil - Isabel Cristina G Leite; Francisco José Roma Paumgartten; Sérgio Koifman (Instituto Materno Infantil de Pernambuco, 2005)
OBJETIVOS: avaliar a associação deste grupo de malformações e determinadas condições de saúde materna. MÉTODOS: estudo caso-controle reunindo 274 portadores de fendas lábio-palatinas e 548 controles hospitalares. As medidas de risco (odds ratio: OR), foram obtidos a partir da análise de regressão logística condicional. RESULTADOS: as principais associações foram o relato de malformações maternas (OR 8,01; IC95%: 2,23-28,81); infecções ginecológicas (OR 2,77; IC95%: 1,50-5,10); distúrbios neurológicos (OR 7,11; IC95%: 2,57-19,75); viroses (resfriados comuns, por exemplo) (OR 7,57; IC95%: 2,46-23,32). Na história reprodutiva, nenhuma condição foi estatisticamente significantes, no entanto, abortos espontâneos prévios (OR 1,42; IC95%: 0,95-2,13) e natimortos (OR 2,22; IC95%: 0,88-5,65) exibiram maior magnitude de risco. Além do uso de anticonvulsivantes (OR 20,00; IC95%: 3,36-437,97), outros grupos de medicamentos atuaram como fatores de risco, como analgésicos (OR 1,45; IC95%: 1,08-1,95); antibióticos (OR 2,43; IC95%: 1,33-4,57); antifúngicos (OR 9,00; IC95%: 2,14-61,12) e chás (OR 4,09; IC95%: 2,23-7,77). CONCLUSÕES: ao lado de exposições já descritas na literatura, como aquela relativa ao uso de anticonvulsivantes, outras tantas foram identificadas. Embora possam ter sofrido a influência de fatores de confundimento e viés de memória, que podem afetar os resultados deste estudo elas devem ser avaliadas servindo de subsídio para estudos mais específicos. OBJECTIVES: to evaluate the association of this malformation group and specific conditions of maternal health. METHODS: case control study with 274 individuals with cleft lip and palate and 548 hospital controls. The odd ratio (OR) and confidence intervals were obtained based on conditional logistic interval analysis. RESULTS: the main associations were maternal malformation reports (OR 8,01; 95%IC%: 2,23-28,81); gynecological infections (OR 2,77; 95%IC: 1,50-5,10); neurological conditions (OR 7,11; IC95%: 2,57-19,75); viruses (common cold for example) (OR 7,57; 95%IC: 2,46-23,32). In reproductive history no condition was demonstrated as being statistically significant, nevertheless, previous spontaneous abortions (OR 1,42; 95%IC: 0,95-2,13) and stillborns (OR 2,22; 95%IC: 0,88-5,65) demonstrated more pronounced risks. In addition to the use of anticonvulsant drugs (OR 20,00; 95%IC: 3,36-437,97), other drug groups were indicated as risk factors such as analgesics (OR 1,45; 95%IC: 1,08-1,95); antibiotics (OR 2,43; 95%IC: 1,33-4,57); antifungical drugs (OR 9,00; 95%IC: 2,14-61,12) and teas (OR 4,09; 95%IC: 2,23-7,77). CONCLUSIONS: together with exposures already described in the literature, including the use of anticonvulsant drugs, many others were identified. Although they may have been affected by possible mental confusion and forgetfulness that could have affected the results of this study, they should be evaluated and used as subsidies to more specific studies.